2016
DOI: 10.1088/1361-6560/61/24/8875
|View full text |Cite
|
Sign up to set email alerts
|

An improved asymmetric gradient coil design for high-resolution MRI head imaging

Abstract: For head magnetic resonance imaging, local gradient coils are often used to achieve high solution images. To accommodate the human head and shoulder, the head gradient coils are usually designed in an asymmetric configuration, allowing the region-of-uniformity (ROU) close to the coil's patient end. However, the asymmetric configuration leads to technical difficulties in maintaining a high gradient performance for the insertable head coil with very limited space. In this work, we present a practical design conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…However, PNS thresholds are already severely limiting the useable gradient performance for whole-body coils due to the larger area of tissue exposed to the rapidly switching fields, and only modest gains are expected in the future. It is especially for this reason that high-performance human-head-sized insertable GCs have been proposed (Chronik and Rutt, 1998; Chronik et al, 2000; Tomasi et al, 2002; Wong, 2012; Handler et al, 2014; Tang et al, 2016). A number of these designs are suitable for UHF but may not have the thermal and electrical performance to tolerate the high duty cycles, currents and slew rates required for high-quality UHF imaging.…”
Section: Dedicated Gradient Concepts Suitable For Uhfmentioning
confidence: 99%
“…However, PNS thresholds are already severely limiting the useable gradient performance for whole-body coils due to the larger area of tissue exposed to the rapidly switching fields, and only modest gains are expected in the future. It is especially for this reason that high-performance human-head-sized insertable GCs have been proposed (Chronik and Rutt, 1998; Chronik et al, 2000; Tomasi et al, 2002; Wong, 2012; Handler et al, 2014; Tang et al, 2016). A number of these designs are suitable for UHF but may not have the thermal and electrical performance to tolerate the high duty cycles, currents and slew rates required for high-quality UHF imaging.…”
Section: Dedicated Gradient Concepts Suitable For Uhfmentioning
confidence: 99%
“…Gradient coils with higher peak amplitude (G max ) and peak slew rate are desired to improve image quality and speed for echo planar imaging, diffusionweighted imaging and several other advanced imaging protocols (Le Bihan et al, 1986;Young et al, 1987;Turner et al, 1990;Wong et al, 1991;Basser and Pierpaoli, 1996), and significant research efforts are being carried out to develop such coils. Local head/neck gradient coils have been evaluated and developed to improve gradient performance compared to whole-body gradient coils (Alsop and Connick, 1996;Crozier et al, 1999;Chronik et al, 2000;Tang et al, 2016). High-performance research systems for imaging human brain connectivity and microstructure have been developed with G max of 300 mT/m (McNab et al, 2013) or slew rate of 1200 T/m/s (Weiger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Previous reports of smaller-diameter, dedicated headgradient coils have shown that the PNS threshold is substantially above that of whole-body gradients, allowing the use of gradient slew rates in excess of 200 T/m/s. [5][6][7] However, other head gradient coils developed for imaging the brain have not seen routine use, due either to deficiencies in active shielding, poor spatial linearity over the required 22-cm to 24-cm imaging FOV for brain imaging, 5,[8][9][10][11][12][13][14][15] gradient heating, or the additional concomitant fields produced by an asymmetric design. 16,17 Regions of the brain such as the frontal lobe and the cerebellum could not be imaged without distortion as a result of poor spatial gradient linearity.…”
Section: Introductionmentioning
confidence: 99%